Improvement In Kidney Damage Resulting From Stanozolol Intramuscular Injections In Rats By Natural Cocoa Powder (NCP) Administration - Odoom, D.; Arko-Boham, B.; Adutwum-Ofosu, K.K.; Blay, R.M.; Adjenti, S.K.; Ahenkorah, J.; Hottor, B.A.; et al. (Scientific African, 2024)
Background: Stanozolol, an anabolic steroid, has been shown to induce kidney damage through mechanisms involving oxidative stress and inflammation. Natural Cocoa Powder (NCP), known for its high antioxidant content, may offer protective effects against such damage. Aim: This study aimed to evaluate the potential of Natural Cocoa Powder (NCP) in ameliorating kidney damage caused by stanozolol intramuscular injections in rats. Methods: Thirty rats were randomly assigned into five groups (G1–G5) and fed with standard rat chow. G1 and G3 received 2 mg/kg stanozolol intramuscularly twice weekly, G2 and G4 received 5 mg/kg stanozolol twice weekly, while G5 served as the control with no stanozolol. G1, G2, and G5 had 24 h access to water, while G3 and G4 had water replaced with 2 % NCP from 6 am to 6 pm daily. After 8 weeks, kidneys were perfusion-fixed and analyzed histomorphometrically for proximal/distal tubules, Bowman’s space, glomerular tuft, and renal corpuscle composition. Before and after treatments, renal function was measured by serum creatinine and blood urea nitrogen, whilst systemic inflammation was monitored by erythrocyte sedimentation rate and serum C-reactive protein tests. Results and Discussion: Stanozolol administration significantly increased kidney damage in a dose-dependent manner, with marked rises in the volume densities of the proximal convoluted tubule (PCT), distal convoluted tubule (DCT), glomerular tuft, and renal corpuscle. At higher doses, PCT and DCT volume densities increased by 143 % and 223 %, respectively, compared to controls. Natural cocoa powder (NCP) mitigated these effects, reducing PCT, DCT, and glomerular tuft volume densities by 92 %, 77 %, and 86 %, respectively. Stanozolol also elevated serum markers of kidney dysfunction and inflammation, such as blood urea nitrogen (BUN), serum creatinine.
Research Article
Keywords: Anabolic androgenic steroids; Nephrotoxicity; Anti-oxidation; Anti-inflammation; Flavanols; Natural cocoa powder